FAKTOR INTERNAL DAN EKSTERNAL YANG MEMPENGARUHI KINERJA KEUANGAN PDAM KOTA SURAKARTA - Riyadi, Agung (Semarang State University, 2009)
This research had an aims to analyse financial performance of PDAM, to analyse the internal andexternal factors that influenced financial performance of PDAM and to analyse the most dominant factoramong internal and external factors.This research reached the aims with the theory of financial performance, the theory of public goodsand the theory of turbulency economy. Mixing of all the theories brought to the hyphotesis that theinternal factors like price of water, revenue, and cost and the external factors like rate of inflation andexchange rate influenced financial performance of PDAM. This research used OLS without constantaregresion equation and ChowÃ¢â¬â¢s test to test the hyphotesis.This research showed that PDAM financial performance was good and consisted of debt structureperformance, financial efficiency performance, and profit performance. The internal and external factorsbuilt a linkage that influenced the financial performance. The internal factors that influenced the financialperformance were price of water, revenue, and cost. The external factors that influenced the financialperformance were rate of inflation and exchange rate. The most dominant factor was revenue. Thisresearch also showed that PDAM applied average cost pricing.Keywords: internal and external factors, regulated price, financial performance